(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Workplace demands have grown steadily more complex, and the capacity of employees to regulate emotion while sustaining a workable boundary between professional and personal domains has become a matter of practical as well as theoretical interest. This paper examines the association between emotional intelligence and work-life balance among 134 full-time employees drawn from technical and non-technical occupations, and additionally tests whether gender and occupational category shape either construct independently or in combination. Emotional intelligence was measured using the Wong and Law Emotional Intelligence Scale, and work-life balance was assessed through an adapted version of Hayman’s three-dimensional scale. Pearson correlation revealed a moderate, statistically significant positive association between emotional intelligence and work-life balance (r = .331, p < .001), suggesting that employees who read and manage their own emotional states with greater facility also report a more sustainable balance between work and personal commitments. A 2 × 2 factorial ANOVA indicated a significant main effect of gender on emotional intelligence, with male employees reporting somewhat higher scores than female employees, while job type produced no discernible effect and the gender-by-job-type interaction remained non-significant. Work-life balance, by contrast, did not vary meaningfully by gender, job type, or their interaction. These results are discussed with reference to the Conservation of Resources framework and existing literature on emotional competence in Indian organizational settings, and practical implications for workplace training are outlined.